THE AUTONOMY OF REASON AND MORAL NORMS IN THE THOUGHT OF IBN RUSHD: A CONCEPTUAL RECONSTRUCTION OF ISLAMIC ETHICS - Nabila Agustiana; Elvira Purnamasari (UIN Sumatera Utara Medan, 2026)
Abstract: This study examines the concept of rational autonomy and moral norms in the thought of Ibn Rushd as an effort to reconstruct a more rational and contextual Islamic ethics. The background of this research lies in the persistent dichotomy between reason and revelation in understanding Islamic ethics, which often results in partial and less adaptive approaches to contemporary moral challenges. The purpose of this study is to analyze the role of rational autonomy in shaping moral norms and its relevance to the development of modern Islamic ethics. This research employs a qualitative approach with a library research method, using descriptive-analytical techniques through philosophical and historical perspectives. The findings reveal that Ibn Rushd positions reason as an epistemological instrument with legitimate authority to understand revelation and to determine moral values rationally. Rational autonomy, in his view, is not absolute but operates within the framework of Islamic law, allowing contextual interpretation of religious texts. Moral norms are therefore not merely normative but also possess rational and teleological dimensions oriented toward public welfare (maslahah). The study concludes that the integration of reason and revelation in Ibn Rushd’s thought provides a foundational framework for reconstructing Islamic ethics that is more adaptive, inclusive, and relevant to contemporary moral issues.Keywords: rational autonomy; moral norms; Islamic ethics; Ibn Rushd; ethical reconstruction